Non-breeding Ethology of Spot-billed Pelican (Pelecanus philippensis) at Adyar Eco-Park, Chennai, India - Meghna Bandyopadhyay; Rishin Basu Roy; Arijit Chatterjee (Journal of Tropical Life Science, 2014)
Spot-billed Pelican is a Near Threatened species according to IUCN red list. There are very limited studies regarding the non-breeding behavior of the Spot-billed Pelican, where behavioural study is very important to understand the species and ecosystem to which they belong. Studying ethology is an important stepping stone for the conservation of the species and its ecosystem. With this aspect an ethological study was carried out at Adyar Eco-park Chennai during the non-breeding season of Spot-billed Pelican for a period of thirteen days continuously. An Ad libitum study was adapted to document their behaviour. The observation was conducted over a period of 7 different time schedules. From the observation 14 individual behaviours and 4 conspecific and group behaviours were recorded. The four most time consuming activities are Alert (193.13 min, 31.15%), Preening (92.36 min, 14.89%), Resting (81.13 min, 13.09%) and Looking around (71 min, 11.45%). The mean population density in the study area showed a declining trend from dawn to noon (2.04-0.55 individuals per 100 sq. m.) and increasing from noon to evening (0.55-3.81 individuals per 100 sq. m.). During the observation it was found that this area is a non-breeding roosting site for the bird and they show some typical pattern as the day progresses. The present study can be helpful to build a comprehensive conservation programme for the Spot-billed Pelican and management plan for Adyar Eco-park can be developed if carried out for a longer period of time.